2003
DOI: 10.1161/01.cir.0000084505.54603.c7
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Seropositivity Is Associated With Impaired Vascular Function

Abstract: Background-Herpesvirus infection is a possible risk factor for atherogenesis, and diabetics may be at particular risk.Endothelial dysfunction is an early marker for atherosclerosis, and the present study tests the hypotheses that (1) prior infection with cytomegalovirus (CMV) and herpes simplex virus (HSV) is associated with endothelial dysfunction and (2) this may be more marked in diabetics. Methods and Results-Serum samples were tested for anti-IgG antibodies to CMV and HSV from 400 subjects (mean age for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 30 publications
1
87
0
1
Order By: Relevance
“…As the documentation of Enhanced cytomegalovirus infection in atherosclerotic human blood vessels, causing hypertension has been concluded. 35 And the Detection of human cytomegalovirus DNA, RNA, and antibodies in normal donor blood. 35 Antiviral infusions with the neuronal complimentary drugs were administered twice a day for 10 days.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the documentation of Enhanced cytomegalovirus infection in atherosclerotic human blood vessels, causing hypertension has been concluded. 35 And the Detection of human cytomegalovirus DNA, RNA, and antibodies in normal donor blood. 35 Antiviral infusions with the neuronal complimentary drugs were administered twice a day for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…35 And the Detection of human cytomegalovirus DNA, RNA, and antibodies in normal donor blood. 35 Antiviral infusions with the neuronal complimentary drugs were administered twice a day for 10 days. Vitals were recorded every 4 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ji et al conducted an aggregate data metaanalysis involving 9,000 patients with CAD and 8,608 controls from a total of 55 studies, and concluded that CMV infection was associated with an increased risk of CAD (24). In this regard, some suggested potential mechanisms include vessel wall colonization, enhancement of body's pre-existing inflammatory response to risk factors such as hyperlipidemia, destabilization of the pre-existing plaques by activating the immune response, endothelial dysfunction, or even cross-reaction of the anti-CMV antibodies with heat shock proteins during the CMV infection and the subsequent apoptosis of the non-stressed endothelial cells (16,(25)(26)(27)(28)). Yet, the most accepted mechanism through which CMV may contribute to atherogenesis is provocation of inflammatory response in the host (29).…”
Section: Cytomegalovirus Infection and Coronary Artery Disease: A Sinmentioning
confidence: 99%